The unsung patriot memoirs of Wong Pow Nee - Wong, Peter Tet Phin; Koay, Su Lyn (Bumblogger Connexion Marketers, 2014)
The Unsung Patriot: Memoirs of Wong Pow Nee is a record of Pow Nee's impeccable journey in writing national history - rising from humble beginnings as a farmer and school teacher to public office as the first Chief Minister of Penang from 1957 to 1969. Apart from rare insights and accounts of Pow Nee's early services and personal life, this book seeks to fill in the gaps of Penang's post-independence developmental history, while highlighting Pow Nee's personal struggles and major contributions during his turbulent tenure as Chief Minister. Literally and little known, Pow Nee paved the way for the birth of Penang's industrialisation, typically on the mainland portion of the state, which later turned out a huge success under his successor, Dr. Lim Chong Eu. All of these are significant events in Penang's modern history that mark the state's impressive transformation from 'swamps to semiconductors'. Also, in uncovering the bits and pieces of national history, this book equally sheds light on Pow Nee's ambassadorial role to Rome and his involvement in the Cobbold Commission of 1962, tasked with the responsibility of gathering opinions from East Malaysia for the formation of Malaysia. Although these formed a relatively small part of Malaysia's rich history, Pow Nee had nevertheless played a significant role in the nation's building process as a whole including that of Penang.